2006
DOI: 10.1002/hed.20466
|View full text |Cite
|
Sign up to set email alerts
|

Epstein‐Barr virus (EBV) serology for predicting distant metastases in a white juvenile patient with nasopharyngeal carcinoma and no clinical response to EBV lytic induction therapy

Abstract: In contrast to EBV DNA load, EBV serology was useful in predicting distant NPC metastasis after initial complete remission in this patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…All 3 patients showed a biological response to CLVA therapy indicated by an increase in viral DNA load in the blood, as observed in a previous case study (14). This increase reflects fragmented EBV DNA derived from apoptotic tumor cells (29).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…All 3 patients showed a biological response to CLVA therapy indicated by an increase in viral DNA load in the blood, as observed in a previous case study (14). This increase reflects fragmented EBV DNA derived from apoptotic tumor cells (29).…”
Section: Discussionsupporting
confidence: 75%
“…Besides tumor cell apoptosis induced by GCb, it could reactivate EBV within the tumor cells. The potential for EBV lytic induction by GCb in EBV-positive NPC cell lines was shown to be higher than by 5-FU, which was used in a previous juvenile NPC case study (14,25,26). Activation of highly methylated DNA of latent EBV can be enhanced by epigenetic chromatin remodeling of the EBV genome induced by HDAC inhibitors and DNA-demethylating agents (7)(8)(9)(10)(11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because immunoblot studies revealed a diagnostic value of multiple EBV proteins, in particular certain EBV-EA markers, we recently developed a separate IgA EA ELISA using native EA proteins (22). In addition to their role in primary diagnosis, anti-EBV IgA responses, in particular the IgA EA response, also have a distinct role for posttreatment follow-up monitoring, as declining responses correlate with a good prognosis and increasing responses are related to persistence of relapsing tumor (6,16,24). The availability of two distinct and biochemically well-defined EBV IgA ELISA systems addressing responses to different EBV antigens for NPCspecific serology may add to further standardization.…”
mentioning
confidence: 99%
“…NPC is characterized by aberrant immunoglobulin G (IgG) and particularly IgA responses directed against various latent and lytic EBV antigens (13). These aberrant responses have diagnostic relevance in screening for early-stage and posttreatment monitoring (7,22,23,43). The diagnosis and screening of NPC are done mostly by indirect antibody detection using cell spot slide tests, one of the earliest serology methods developed, which to date is still used as a "gold standard" (8,35).…”
mentioning
confidence: 99%